“Shelter from the Storm:” Do Partnerships Buffer Well-Being Costs of Unemployment? - Prechsl, Sebastian; Wolbring, Tobias (2022)
This paper contributes to the existing literature on the effects of unemployment on subjective well-being (SWB) by partnership status. We argue that material and latent deprivation can explain effects of unemployment on SWB by partnership status, as both partners and their employment status crucially shape the extent of deprivation. To test our hypothesis about partner-specific unemployment effects on SWB and the mediating roles of latent deprivation (in terms of status loss) and of material deprivation, we use fourteen waves of German panel data. To identify time-varying unemployment effects, we rely on time-distributed fixed effects models. Our results suggest a strong negative and rather time-constant impact of unemployment on SWB, buffered over time for those with working or non-working partners. Further, our results indicate material deprivation and status loss to be relevant mechanisms for explaining partner-specific trajectories in the loss of SWB.</
Keywords: Subjective well-being; unemployment; partnership status; buffering; panel data; Gender